Love or Money: Vocational Attitudes of the Catholic School Teacher - Cimino, SSJ, Carol (Catholic Education: A Journal of Inquiry and Practice, 2001)
Public and private schools experience teacher shortages today, but the problem is acute in Catholic schools. Reasons given for the shortage in Catholic schools include salaries and benefits. Have teachers’ views of teaching in a Catholic school changed from teaching as ministry or vocation to teaching as merely a job? This study discusses the sense of teaching as vocation among a sample of Catholic high school and elementary school teachers in the state of New York. It ascertains the sense of vocation among these teachers; correlates financial considerations with the sense of vocation; and illustrates that religious preference and practice, years of teaching and ownership, and presence of religious men and women affect how teachers see their job as ministry.